Modeling the relationship between the main emulsion components and stability, viscosity, fluid behavior, zeta-potential, and electrophoretic mobility of orange beverage emulsion using response surface methodology - Mirhosseini, H; Tan, CP; Hamid, NSA; Yusof, S (Amer Chemical Soc, 2024)
The possible relationships between the main emulsion components (namely, Arabic gum, xanthan gum, and orange oil) and the physicochemical properties of orange beverage emulsion were evaluated by using response surface methodology. The physicochemical emulsion property variables considered as response variables were emulsion stability, viscosity, fluid behavior, xi-potential, and electrophoretic mobility. The independent variables had the most and least significant (p < 0.05) effect on viscosity and xi-potential, respectively. The quadratic effect of orange oil and Arabic gum, the interaction effect of Arabic gum and xanthan gum, and the main effect of Arabic gum were the most significant (p < 0.05) effects on turbidity loss rate, viscosity, viscosity ratio, and mobility, respectively. The main effect of Arabic gum was found to be significant (p < 0.05) in all response variables except for turbidity loss rate. The nonlinear regression equations were significantly (p < 0.05) fitted for all response variables with high R-2 values (> 0.86), which had no indication of lack of fit. The results indicated that a combined level of 10.78% (w/w) Arabic gum, 0.56% (w/w) xanthan gum, and 15.27% (w/w) orange oil was predicted to provide the overall optimum region in terms of physicochemical properties studied. No significant (p > 0.05) difference between the experimental and the predicted values confirmed the adequacy of response surface equations.